Thermal processing reduces PFAS concentrations in blue food – A systematic review and meta-analysis. (1st July 2022) - Vendl, Catharina; Pottier, Patrice; Taylor, Matthew D.; Bräunig, Jennifer; Gibson, Matthew J.; Hesselson, Daniel; Neely, G. Gregory; Lagisz, Malgorzata; Nakagawa, Shinichi
Abstract: Per- and polyfluoroalkyl substances (PFAS) are ubiquitous in the environment and often ingested with food. PFAS exposure in people can have detrimental health consequences. Therefore, reducing PFAS burdens in food items is of great importance to public health. Here, we investigated whether cooking reduces PFAS concentrations in animal-derived food products by synthesizing experimental studies. Further, we examined the moderating effects of the following five variables: cooking time, liquid/animal tissue ratio, cooking temperature, carbon chain length of PFAS and the cooking category (oil-based, water-based & no-liquid cooking). In our systematic review searches, we obtained 512 effect sizes (relative differences in PFAS concentration between raw and cooked samples) from 10 relevant studies. These studies exclusively explored changes in PFAS concentrations in cooked seafood and freshwater fish. Our multilevel-meta-analysis has revealed that, on average, cooking reduced PFAS concentrations by 29%, although heterogeneity among effect sizes was very high ( I 2 = 94.65%). Our five moderators cumulatively explained 49% of the observed heterogeneity. Specifically, an increase in cooking time and liquid/animal tissue ratio, as well as shorter carbon chain length of PFAS (when cooked with oil) were associated with significant reductions in PFAS concentrations. The effects of different ways of cooking depended on the other moderators, while the effect of cooking temperature itself was not significant. Overall, cooking can reduce PFAS concentrations in blue food (seafood and freshwater fish). However, it is important to note that complete PFAS elimination requires unrealistically long cooking times and large liquid/animal tissue ratios. Currently, literature on the impact of cooking of terrestrial animal produce on PFAS concentrations is lacking, which limits the inference and generalisation of our meta-analysis. However, our work represents the first step towards developing guidelines to reduce PFAS in food via cooking exclusively with common kitchen items and techniques. Graphical abstract: Image 1 Highlights: Our meta-analysis explores the effects of cooking on PFAS loads in animal produce. Cooking can reduce PFAS concentrations in blue food (i.e., seafood). Longer cooking and larger relative volume of cooking media favours PFAS reduction. Shorter chain PFAS decrease more in oil-based cooking than longer chain PFAS. The lack of data on terrestrial species needs to be addressed in future studies.